Fortification of Yogurt with Moringa Leaf Extract (Moringa oleifera) on Quality and Quality as a Functional Food: A Review - Azis, Rosidi; Lestari, Juniarti Wulan; Puspaningsih, Eunike Sri; Muqtafiah (Universitas Kristen Cipta Wacana, 2025)
The incorporation of natural bioactive compounds into dairy products has gained increasing attention due to their potential to enhance nutritional value and functional properties. Moringa oleifera, commonly known as the drumstick tree, is a nutrient-dense plant rich in polyphenols, flavonoids, vitamins, and minerals, making it a promising candidate for yoghurt fortification. This review evaluates the impact of Moringa oleifera leaf extract on the physicochemical, microbiological, antioxidant, and sensory attributes of yoghurt. Data from recent studies (2014 - 2024) indicate that the addition of Moringa oleifera extract at concentrations up to 0.5% significantly improves total phenolic content, antioxidant activity (DPPH and ABTS assays), water holding capacity (WHC), and viscosity, while maintaining acceptable pH levels and supporting probiotic viability. However, higher concentrations may lead to undesirable sensory characteristics such as astringency and greenish coloration, which can affect consumer acceptance. Optimization of extraction methods, fortification levels, and formulation strategies such as encapsulation or blending with other natural ingredients is recommended to balance functionality and sensory appeal. Overall, yoghurt fortified with Moringa oleifera extract demonstrates potential as a functional food with enhanced antioxidant properties and improved nutritional profile. Further research is needed to assess long-term stability and in vivo health benefits.